Níveis de aminoácidos digestíveis para juvenis de tambaqui, Colossoma macropomum e turnover isotópico do carbono - 13 e do nitrogênio - 15 no tecido muscular - Nascimento, Thiago Matias Torres do [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Three experiments were conducted to determine the amino acid digestibility of the principal ration ingredients fed to juvenile tambaqui (Colossoma macropomum), to estimate this species' requirements for digestible amino acids and with this information, to evaluate the effect of lysine and/or methionine supplementation in diets on the turnover of stable carbon-13 and nitrogen-15 isotopes in muscle tissue. In the first study, 390 tambaqui juveniles (70 ± 8.6 g) were used to evaluate the apparent digestibility coefficients (ADC) of the amino acids (AA) of thirteen common feed ingredients. For energy feedstuffs, high digestibility values for all essential amino acids were observed for corn (94.60%) and wheat middling (91.93%) and lower values for broken rice (75.66%) and sorghum (72.84%). For protein feedstuffs, the apparent digestibility coefficients (ADC) for both essential amino acids (EAA) and non-essential amino acids (NEAA) were high (79.47 to 98.46%), with the exception of alchool yeast (68.44% for EAA and 76.68% for NEAA). For most of the foods studied, tryptophan was found to be the most limiting AA, with the lowest chemical scores (6.21 to 51.25). However, lysine was found to be the first limiting for wheat middling, corn gluten and soybean meal. Soybean meal was the most complete food as respects to the amino acid profile, with an index of digestible essential amino acids (IAAE) of 102.38%, unlike wheat gluten, which had the lowest IAAE at 48.03%. In the second test, dose response was carried out to determine the digestible lysine requirements for tambaqui. The nutritional requirements of other amino acids could be estimated from the lysine requirements, thereby designing an amino acid profile (called ideal protein) through the relationship between the best digestible dietary lysine and the amino acid profile of white tambaqui muscle. Fish with an average weight of 7.74 ± 1.01g were fed diets containing seven ...

Três experimentos foram conduzidos para determinar a digestibilidade de aminoácidos dos principais alimentos utilizados na alimentação de juvenis de tambaqui (Colossoma macropomum), estimar a exigência em aminoácidos digestíveis para esta espécie e com estas informações avaliar o efeito da suplementação de lisina e/ou metionina em dietas práticas no turnover dos isótopos estáveis de carbono-13 e nitrogênio-15 em tecido muscular. No estudo 1, foram utilizados 390 juvenis de tambaqui (70 ± 8,6 g) para avaliar os coeficientes de digestibilidade aparente (CDA) dos aminoácidos (AA) de trezes alimentos. Para os alimentos energéticos, altos valores de digestibilidade para todos os aminoácidos essenciais foram observados para o milho (94,60%) e o farelo de trigo (91,93%) e menores para a quirera de arroz (75,66%) e o sorgo (72,84%). Para os alimentos proteicos, em geral, os valores médios dos coeficientes de digestibilidade aparente (CDA) de aminoácidos essenciais (AAE) e aminoácidos não essenciais (AANE) foram elevados (de 79,47 a 98,46%), com exceção da levedura de álcool (68,44% para AAE e 76,68% para AANE). O triptofano foi o aminoácido que apresentou-se como o mais limitante para maioria dos alimentos estudados, com os menores escores químicos (de 6,21 a 51,25), exceto para o farelo de trigo, glúten de milho e farelo de soja em que a lisina foi o primeiro limitante. O maior índice de aminoácidos essenciais digestíveis (IAAE) foi apresentado pelo farelo de soja (102,38%), que foi o alimento mais completo em relação ao perfil de aminoácidos, ao contrário do glúten de trigo, que apresentou o menor IAAE (48,03%). Realizou-se o ensaio 2, de dose resposta, para determinar a exigência nutricional em lisina digestível para juvenis de tambaqui e desta forma estimar as exigências nutricionais dos outros aminoácidos. Os peixes com peso médio de 7,74 ± 1,01g foram alimentados com sete dietas contendo os ...
Keywords: Peixe - Nutrição; Tambaqui (Peixe); Aminoacidos; Proteínas; Isótopos estáveis; Lisina na nutrição animal; Metionina; Amino acids